Coordination Between Implementing Organizations In The Implementation Of Stunting Reduction Policies In Bulukumba District - Febriani, Andi Citra; Rusdi, Muhammad Rusdi (Universitas Muhammadiyah Makassar, 2025)
Reducing stunting is a national development priority that requires cross-sectoral policy implementation and inter-organizational coordination. Bulukumba District has achieved a significant reduction in stunting prevalence, but policy implementation still faces coordination challenges among implementing agencies. This study analyzes inter-organizational coordination in the implementation of stunting policies in Bulukumba District. A qualitative approach was used through in-depth interviews, observations, and document analysis involving key stakeholders. The results show that cross-sector coordination mechanisms have been established through the TPPS and joint planning forums, but challenges remain in the consistency of data communication, differing perceptions of roles among agencies, and limited integration of information systems. These results indicate that effective stunting policy implementation depends not only on the availability of programs, but also on the quality of inter-organizational coordination.